(untitled) - Đỗ, Tuấn Minh (Hà Nội, 2006)
Sách gồm 16 bài, mỗi bài có 5 phần: Reading, Listening, Speaking, Writing và Language focus.
Keywords: English language,Tiếng Anh; Study and teaching (Secondary),Dạy và học (Trung học)